IMPLEMENTASI PENDIDIKAN KARAKTER DISIPLIN DAN TANGGUNG JAWAB BERBASIS TRADISI PESANTREN DI SMP PLUS AL HADI TUBAN - Widayati, Lissa; Wijaya, Rahmanu (Universitas Negeri Surabaya (Unesa), 2024)
This study is driven by the current educational reality, which shows a decline in quality, particularly in the affective education of students. This has led to a deterioration in the morality of the younger generation, evidenced by the prevalence of actions that deviate from values and norms, such as corruption, juvenile delinquency, cheating, and skipping school. Therefore, it is essential to integrate character education values into children, especially in pesantren-based schools aimed at forming noble character (akhlakul karimah). Discipline and responsibility are vital aspects of school activities and are essential, encompassing attitudes, behaviors, motivations, and skills. Character education plays a crucial role in creating quality and potential individuals. This research aims to describe the implementation of character education focusing on discipline and responsibility based on pesantren traditions at SMP Plus Al Hadi Tuban. Using a qualitative approach with a case study method, data collection techniques include observation, interviews, and documentation. Data analysis involves collection, reduction, presentation, and verification. The theoretical foundation used is Thomas Lickona's character education theory. The results indicate that the implementation of character education focusing on discipline and responsibility at SMP Plus Al Hadi is generally optimal. Character education is incorporated into every lesson and integrated into extracurricular activities, teaching students to be disciplined and responsible. Additionally, the habituation of positive activities such as istighosah, morning assembly, communal prayers, and dhuha prayer reflects discipline and responsibility.